Increase in leaf temperature opens stomata and decouples net photosynthesis from stomatal conductance in Pinus taeda and Populus deltoides x nigra - Urban, Josef; Ingwers, Miles W; McGuire, Mary Anne; Teskey, Robert O (Journal of Experimental Botany, 2017)
The effect of temperature on stomatal conductance (gs) and corresponding gas exchange parameters was studied in two tree species with contrasting leaf anatomy and ecophysiology-a broadleaf angiosperm, Populus deltoides x nigra (poplar), and a needle-leaf gymnosperm, Pinus taeda (loblolly pine). Experiments were conducted in growth chambers across a leaf temperature range of 19-48°C. Manipulations of temperature were done in well-watered and drought soil conditions and under ambient (400 ppm) and elevated (800 ppm) air CO2 concentrations. Increases in leaf temperature caused stomatal opening at both ambient and elevated [CO2]. The gs increased by 42% in poplar and by 40% in loblolly pine when leaf temperature increased from 30°C to 40°C at a vapour pressure difference of 1 kPa. Stomatal limitation to photosynthesis decreased in elevated temperature in loblolly pine but not in poplar. The ratio of net photosynthesis to gs depended on leaf temperature, especially at high temperatures. Evaporative cooling of transpiring leaves resulted in reductions in leaf temperature up to 9°C in well-watered poplar but only 1°C in drought-stressed poplar and in loblolly pine. As global mean temperatures rise and temperature extremes become more frequent and severe, understanding the effect of temperature on gs, and modelling that relationship, will become increasingly important.
Keywords: listy rostlin; Populus; Plant Leaves; Plant Transpiration; transpirace rostlin; Pinus taeda; Plant Stomata; Hot Temperature; fotosyntéza; vysoká teplota; borovice kadidlová; Droughts; období sucha; Photosynthesis; průduchy rostlin